2020
DOI: 10.1159/000507828
|View full text |Cite
|
Sign up to set email alerts
|

CASC9 Facilitates Cell Proliferation in Bladder Cancer by Regulating CBX2 Expression

Abstract: Background: As the seventh most common urologic carcinoma worldwide, approximately 430,000 patients are diagnosed with bladder cancer (BC) every year. Increasing evidence indicates that long noncoding RNAs (lncRNAs) play crucial roles in the progression of BC. Objectives: This study is aimed to explore the function and mechanism of CASC9 in BC. Methods: Bioinformatics analysis and experiments including RT-qPCR, luciferase reporter, Cell Counting Kit-8 assay, Western blot, RNA immunoprecipitation assay, and TU-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…As the important components of the epigenetic regulatory complexes, CBX family proteins are involved in the development of multiple cancers, including UBC 6 , 7 , 26 , 27 . In this study, we found that CBX7 is the most remarkably downregulated gene among CBX family members in UBC tissues, as compared to normal tissues in TCGA dataset.…”
Section: Discussionmentioning
confidence: 99%
“…As the important components of the epigenetic regulatory complexes, CBX family proteins are involved in the development of multiple cancers, including UBC 6 , 7 , 26 , 27 . In this study, we found that CBX7 is the most remarkably downregulated gene among CBX family members in UBC tissues, as compared to normal tissues in TCGA dataset.…”
Section: Discussionmentioning
confidence: 99%
“…All these and previous findings on CASC9 suggested that CASC9 might be a novel marker for CRC prognosis. In fact, there are many reports that CASC9 is involved in non-small cell lung carcinoma, bladder cancer, thyroid cancer, hepatocellular carcinoma, nasopharyngeal cancer, and lung cancer ( Jin et al, 2019 ; Zeng et al, 2019 ; Chen Y. et al, 2020 ; Huo et al, 2020 ; Zhao et al, 2020 ). It has been suggested that CASC9 is a novel diagnostic, prognostic, and therapeutic target in cancer treatment ( Qian et al, 2020 ; Sharma et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that CASC9 knockdown or silencing reduced cell proliferation, invasion, and migration ( Jin et al, 2019 ; Zhang et al, 2019 ; Chen Y. et al, 2020 ; Ding et al, 2020 ; Fang et al, 2020 ; Huo et al, 2020 ). We are the first to perform similar experiments in CRC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA cancer susceptibility candidate 9 (CASC9) is an lncRNA situated at human 8q21.13 chromosome. Earlier studies have revealed its expression in cases with liver cancer and those with bladder cancer and its association with tumor prognosis [ 12 , 13 ]. Moreover, one recent study has found its expression in cases with colorectal cancer (CRC) [ 14 ], which suggests that lncRNA CASC9 is probably a potential biomarker of CRC.…”
Section: Introductionmentioning
confidence: 99%